Can metastatic lymph node ratio (LNR) predict survival in oral cavity cancer patients?. Issue 4 (24th July 2013) - Sayed, Suhail I.; Sharma, Shilpi; Rane, Pawan; Vaishampayan, Sagar; Talole, Sanjay; Chaturvedi, Pankaj; Chaukar, Devendra; Deshmukh, Anuja; Agarwal, Jai Prakash; D'cruz, Anil K.
Abstract Objectives To evaluate the prognostic role of the lymph node ratio (LNR; ratio of total positive nodes to total dissected nodes) in oral squamous cell carcinoma (OSCC) as compared to pN staging with an aim to provide an optimal cut‐off value. Methods 1, 408 OSCC previously untreated patients who underwent treatment (surgery + neck dissection + adjuvant treatment). LNR sensitivity with respect to survival was calculated using receiver operating characteristic (ROC) curves and Cox regression method. LNR and TNM staging variables were subjected to multivariate analysis. Results LNR (0.088) showed significant association with survival outcomes. For patients with LNR ≤0.088, the OS, DFS, local control, regional control and distant metastasis rates were 64%, 70%, and 89%; for LNR >0.088 it was 22%, 19%, and 52%, respectively (P < 0.001). On multivariate analysis LNR of 0.088 was seen to be an independent prognostic factor for 5‐year regional control (p, hazard ratio [95% confidence interval]; 0.044, 2.016 (1.019–3.990), DFS, 0.032, 1.858 (1.054–3.276), and OS, 0.040, 1.195 (1.033–1.144). On multivariate analysis LNR categorization showed a statistically significant [0.032, 1.858, (1.054–3.276)] advantage over pN staging [0.527, 1.208 (1.054–3.276)] in predicting survival. Conclusions LNR is a better prognostic marker than the current N staging of TNM classification. J. Surg. Oncol. 2013 108:256–263. © 2013 Wiley Periodicals, Inc.